Management and physical features of tribal Kathani cattle of Vidarbha region in Maharatshtra state - KULKARNI, S; BHAGAT, R L; PANDE, A B; GOKHALE, S B (The Indian Journal of Animal Sciences, 2013)
Presently lesser known cattle breed in eastern part of Vidarbha region of Maharashtra state is documented in old gazetteer of Chandrapur district as Telangpatti. During study it was noticed that more popularly this cattle subpopulation is recognized as Kathani. A survey of 1476 animals of different age groups belonging to 389 tribal families from 3 districts Chandrapur, Gadchiroli and Gondia was under taken for studying morpho-metric characteristics along with management practices followed for their animals. Since this breed has not been included in the list of recognized cattle breeds of the country and considering their important role in livelihood of tribal community, an attempt was made to phenotypically characterize the subpopulation. Observations on socio-cultural importance, body measures and general management have been detailed based on the studies of sample. Further study on larger sample for breed characterization is recommended.